Investigation of physicochemical and antioxidant properties of gelatin edible film mixed with blood orange (Citrus sinensis) peel extract. (September 2019) - Jridi, Mourad; Boughriba, Soumaya; Abdelhedi, Ola; Nciri, Hend; Nasri, Rim; Kchaou, Hela; Kaya, Murat; Sebai, Hichem; Zouari, Nacim; Nasri, Moncef
Graphical abstract: Highlights: The drying pretreatment affected negatively the orange peel extract properties. Fresh orange peel extract (FOPE) was successfully incorporated in fish gelatin film (GF). FOPE modified slightly the mechanical and thermal properties of GF. FOPE markedly enhanced the antioxidant properties of the added-GF. Release kinetics of FOPE through GF showed controlled quasi-Fickian diffusion. Abstract: The present study aims at developing Grey triggerfish skin gelatin films containing phenolic extracts from blood orange ( Citrus sinensis ) peel, as an alternative for the existing synthetic packaging films. The effect of drying pretreatment on the phenolic compounds' profile and antioxidant and antibacterial activities of the extracts was investigated. Physicochemical, thermal and mechanical properties of gelatin films incorporated with orange peel extract, at different concentrations and plasticized with glycerol were investigated. Films were also tested for their antioxidant capacity, monitored through the β-carotene bleaching, DPPH radical-scavenging and reducing power activities. Results showed that the fresh orange peel extract (FOPE) was more effective against all bacteria tested and exhibited higher antioxidant effect than the thermally-dried orange peel extract (DOPE). In addition, the LC-ESI-MS analysis showed that the quinic acid was the major compound among the total poly-phenols followed by rutin, trans-ferulic acid, naringenin and 4, 5-di-O-caffeoylquinate. After its addition, FOPE modified the mechanical and thermal properties of gelatin films, which showed more deformable texture than the control gelatin film. This effect may be caused by the interactions between phenolic compounds of the extract and gelatin chains, as assessed by the Fourier Transform infrared (FTIR) analysis. The FOPE-added films presented higher antioxidant properties than the control. Furthermore, release kinetics of FOPE through gelatin film showed controlled quasi-Fickian diffusion. The overall results emphasized the potential use of phenolic compounds from blood orange by-products to produce bioactive films intended for food packaging.